PRELIMINARY STUDY ON CELLULOLYTIC ACTIVITY OF Neoteredo reynei (BARTSCH, 1920) (MOLLUSCA: BIVALVIA: TEREDINIDAE) - Carvalho, Ana Fontenele Urano; Farias, Davi Felipe; Fernandes, Daniel Amorin Oriá; Bezerra, Lady Clarissa Brito Rocha; Queiroz, Liana Rodrigues; Viana, Marina Gomes; Paes, Fernanda Araújo; Barroso, Hortência de Sousa; Mesquita, Paulo César Medeiros; Melo, Vânia Maria Maciel; Barreira, Cristina de Almeida Rocha (Arquivos de Ciências do Mar, 2010)
This work aimed to assess the presence of cellulolytic activity in the microbiote isolated from the digestive tract of Neoteredo reynei and also the presence of cellulolytic activity intrinsic to the animal. To investigate cellulolytic activity in the gastrointestinal microbiote of N. reynei , the mollusks were aseptically dissected and samples of both gastrointestinal epithelium and gastrointestinal content were collected and then inoculated in nutritive agar plates for isolation of bacterial colonies. In order to investigate the mollusk intrinsic cellulolytic activity, some specimens had their whole bodies arbitrarily cut into four regions (shell region, anterior cecum region, posterior cecum region and pallet region) which constituted four different samples. Other specimens had their gastrointestinal content collected to obtain the fifth sample (lumen). All samples were sterilized by treatment with the antimicrobials tetracycline and cetoconazol and then macerated and submitted to cold extraction with sodium phosphate buffer 0.1 M, pH 6.0 (1:1; w/v) for 4 h. Then, extracts were filtered and centrifuged. The supernatant was separated for the cellulolytic assays which were performed in agar cellulose plates by radial diffusion method. Four out of five microbial isolates showed cellulolytic activity. Likewise, all body sections and lumen sterile samples of N. reynei showed cellulolytic activity. Thus, both host microbiote and the mollusk itself seem to be involved in cellulose digestion.